Foot-and-Mouth Disease Virus-like Particles Produced in E. coli as Potential Antigens for a Novel Vaccine - Sang-Cheol Yu; In-Kyu Lee; Hyun-Seok Kong; Sung-Ho Shin; Sung-Yoon Hwang; Yu-Jin Ahn; Jong-Hyeon Park; Bong-Yoon Kim; Young-Cheon Song (Veterinary Sciences, 2025)
Foot-and-mouth disease virus (FMDV) continues to pose a significant threat to livestock health and the global agricultural economy, particularly in endemic regions of Asia, Africa, and the Middle East. Current vaccines based on chemically inactivated FMDV present several challenges, including biosafety risks, high production costs, and limited effectiveness against emerging viral variants. To overcome these limitations, we developed virus-like particle (VLP) vaccines targeting FMDV serotypes O, A, and Asia1 using a recombinant Escherichia coli expression system. The resulting VLPs self-assembled into 25–30 nm particles with native-like morphology and antigenic properties, as confirmed by transmission electron microscopy, SDS-PAGE, and Western blot analysis. Immunogenicity was evaluated in mice and pigs using ELISA and virus neutralization tests (VNT), and protective efficacy was assessed through viral challenge studies. All VLPs induced strong serotype-specific antibody responses, with ELISA PI values exceeding 50% and significantly increased VNT titers after booster immunization. In mice, PD50 values were 73.5 (A-type), 32.0 (O-type), and 55.7 (Asia1-type); in pigs, PD50 values reached 10.6 (O-type) and 22.6 (Asia1-type). Notably, the vaccines induced robust immune responses even at lower antigen doses, suggesting the feasibility of dose-sparing formulations. These findings demonstrate that FMDV VLPs produced in E. coli are highly immunogenic and capable of eliciting protective immunity, highlighting their promise as safe, scalable, and cost-effective alternatives to conventional inactivated FMD vaccines.